Pengembangan Penuntun Praktikum Kimia Sederhana Materi Asam Basa untuk Kelas XI SMA/MA - Reni Afreza; Bayharti Bayharti (Universitas Negeri Padang, 2019)
This research aims to develop a simple chemical practicum guide for acid-base materials, and deterine the level of validity and practicality of the practicum developed. This research includes research and development using the Plomp model. Plomp development model consists of several stage : preliminary or initial investigations, prototype stages and assessment stages. This research was validated by three chemistry lectures of FMIPA UNP and two chemistry teachers at SMAN 11 Solok Selatan. Analysis of research data obtained throught validation sheet. The result of validation have a kappa moment value of 0.84 and practicality value of 0.88 so, can be concluded that the guide developed is very valid and practical